Easy process to obtain suspended graphene flakes on TEM grids - Gonçalves, Hugo Manuel Castro (2015)
Much of the ongoing research on graphene requires free-hanging (suspended) graphene to eliminate any influence from underlying substrates. Several methods have been developed for its preparation but they are either very complex or not completely reliable. Here, we describe a simple method for the transfer of graphene single layers from glass or silicon substrates onto TEM grids. The method uses a carrier film for the transfer process. By optimizing the process yields greater than 60% were achieved. The integrity of the transferred films was confirmed using Raman spectroscopy; successful suspension of both mono- and double-layer graphene sheets was obtained.